(untitled) (The Peerian Journal, 2024)
The risk of VTEO is higher in patients with comorbidities: varicose veins, diabetes mellitus, hypertension, fat metabolism disorder, thromboembolic complications in the history, thrombophilia, malignancies, diseases of the cardiovascular system, in patients with posthemorrhagic anemia and after repeated interventions[1]. The increased risk of developing these complications is noted in women taking hormonal drugs[2]. The main problem of VTEO prevention lies not in the increase in the number of high-risk patients and not in the lack of effective means of prevention, but in the lack of proper organization of prevention, insufficient attention to this problem. To date, VTEO prophylaxis is performed in all surgical patients, but the nature of the applied prophylactic measures is determined by the risk strategy[3]